Umur, Durasi Duduk dan Low Back Pain pada Sopir Bus Trans Mamminasata - Ayu Puspitasari; Nurhikmawati Abdullah; Rezky Aulia Yusuf; Nurul Hikmah Baharuddin; Nurfachanti Fattah (FORIKES, 2023)
Low back pain is a form of work related musculoskeletal disorders. This disorder is often found among workers, including drivers who drive buses. The aim of this study was to analyze the relationship between age and sitting duration and the incidence of low back pain in Trans Mamminasata bus drivers. This research is a quantitative analytical research using a cross-sectional design. This research involved 98 bus drivers selected using accidental sampling technique. Data was collected by filling out a questionnaire, then analyzed using the Chi-square test. The p value in the correlation analysis between age and the incidence of low back pain is 0.000, as well as in the correlation analysis between sitting duration and the incidence of low back pain. Furthermore, it was concluded that age and sitting duration were related to the incidence of low back pain in Trans Mamminasata bus drivers.Keywords: low back pain; bus driver; sitting duration; age ABSTRAK Low back pain merupakan salah satu bentuk dari work related musculoskeletal disorders. Gangguan ini banyak dijumpai pada para pekerja, termasuk para sopir yang mengemudikan bus. Tujuan penelitian ini adalah untuk menganalisis hubungan antara umur dan durasi duduk dengan kejadian low back pain pada sopir bus Trans Mamminasata. Penelitian ini merupakan penelitian kuantitatif analitik dengan menggunakan desain cross-sectional. Penelitian ini melibatkan 98 sopir bus yang dipilih dengan teknik accidental sampling. Data dikumpulkan melalui pengisian kuesioner, lalu dianalisis menggunakan uji Chi-square. Nilai p pada analisis korelasi antara umur dengan kejadian low back pain adalah 0,000, demikian pula pada analisis korelasi antara durasi duduk dengan kejadian low back pain. Selanjutnya disimpulkan bahwa umur dan durasi duduk berhubungan dengan kejadian low back pain pada sopir bus Trans Mamminasata.Kata kunci: low back pain; sopir bus; durasi duduk; umur